The Relationship Between Domain - Yousfi, Noureddine; Mabrouki, Said (Revue jurisprudence; Vol. 11 No 02 (2019): مجلة الاجتهاد القضائي, 2019)
The rights of Intellectual property are considered as moral rights. These rights, which come to non-material things, are the product of human thought and mind. They are developed and applied on the ground to become an intellectual product that may be material or moral. Among these ideas and innovations that has been emerged in recent years is Domain names. This term is often related to the domain of intellectual property in its branches. The reason for this is the novelty of this subject and its relevance to the field of information technology, in addition to the similarities that are associated with concepts of intellectual property such as trademarks and trade names. For example, more domain names in the field of intellectual property its disputes under the laws of similar elements such as the trademark.